DIAGNOSTIC POTENTIAL OF THE ERYTHROCYTIC IMMUNOGLOBULIN DIAGNOSTICUM FOR INDICATION AND IDENTIFICATION OF THE CAUSATIVE AGENTS OF PARTICULARLY DANGEROUS (DEEP) MYCOSES - I. V. Novitskaya; E. V. Prokhvatilova; A. V. Toporkov; D. V. Viktorov; M. Ya. Kulakov; E. V. Savina; V. G. Pushkar’; L. I. Belitskaya; N. A. Osina; Zh. A. Kas’yan; I. V. Shul’gina; O. A. Lobovikova (Проблемы особо опасных инфекций, 2017)
Objective of the study was to assess analytical and diagnostic sensitivity and specificity of the “Reagent kit. Erythrocytic coccidioidomycosal and histoplasmosal immunoglobulin dry diagnosticum”, designed for identification of causative agents of coccidioidomycosis and histoplasmosis in isolated cultures of micromycetes, as well as in clinical and biological samples using indirect hemagglutination test.Materials and methods. The investigation included 264 positive samples (216 samples of micromycete suspensions, 48 samples of biological and clinical material) containing pathogens of histoplasmosis and coccidioidomycosis concentrated up to 3,12·106 and 1,56·106 cells/ml, respectively, and 128 negative samples containing heterologous microorganisms in concentrations equal to 5·106 cells/ml. The study was carried out using biological samples that were artificially contaminated with stated pathogens of particularly dangerous mycoses and samples, obtained from bioassay animals with experimental infection.Results and conclusions. It is established that diagnostic sensitivity of the reagent kit is not less than 99,0 %. The diagnostic specificity is not less than 98,0 %. Reproducibility of the results in all cases was 100 %. The results obtained testify to the prospect of introduction of the developed kit into the health care practice.